CHH Methylation Islands: A Nonconserved Feature of Grass Genomes That Is Positively Associated with Transposable Elements but Negatively Associated with Gene-Body Methylation. (19th June 2021) - Martin, Galen T; Seymour, Danelle K; Gaut, Brandon S
Abstract: Methylated CHH (mCHH) islands are peaks of CHH methylation that occur primarily upstream to genes. These regions are actively targeted by the methylation machinery, occur at boundaries between heterochromatin and euchromatin, and tend to be near highly expressed genes. Here we took an evolutionary perspective by studying upstream mCHH islands across a sample of eight grass species. Using a statistical approach to define mCHH islands as regions that differ from genome-wide background CHH methylation levels, we demonstrated that mCHH islands are common and associate with 39% of genes, on average. We hypothesized that islands should be more frequent in genomes of large size, because they have more heterochromatin and hence more need for defined boundaries. We found, however, that smaller genomes tended to have a higher proportion of genes associated with 5′ mCHH islands. Consistent with previous work suggesting that islands reflect the silencing of the edge of transposable elements (TEs), genes with nearby TEs were more likely to have mCHH islands. However, the presence of mCHH islands was not a function solely of TEs, both because the underlying sequences of islands were often not homologous to TEs and because genic properties also predicted the presence of 5′ mCHH islands. These genic properties included length and gene-body methylation (gbM); in fact, in three of eight species, the absence of gbM was a stronger predictor of a 5′ mCHH island than TE proximity. In contrast, gene expression level was a positive but weak predictor of the presence of an island. Finally, we assessed whether mCHH islands were evolutionarily conserved by focusing on a set of 2, 720 orthologs across the eight species. They were generally not conserved across evolutionary time. Overall, our data establish additional genic properties that are associated with mCHH islands and suggest that they are not just a consequence of the TE silencing machinery.